Bioactivities of Artocarpus chaplasha Roxb. and Bougainvillea spectabillis Willd. (Bangladesh Pharmaceutical Journal, 2013)
The methanol extracts of leaf of Artocarpus chaplasha Roxb. and Bougainvillea spectabillis Willd. as well as their petroleum ether, carbon tetrachloride, chloroform and aqueous soluble partitionates were subjected to screenings for antioxidant, cytotoxic, thrombolytic, membrane stabilizing and antimicrobial activities. The antioxidant potential was evaluated by 1,1-diphenyl-2-picrylhydrazyl (DPPH) and Folin- Ciocalteau reagent using butylated hydroxytolune (BHT) and ascorbic acid as standards. The aqueous soluble fraction of the crude methanol extract of A. chaplasha and the methanolic crude extract of B. spectabillis demonstrated the highest free radical scavenging activity with the IC50 of 15.60±0.27 ?g/ml and 18.33±0.17 ?g/ml, which could be correlated to their total phenolic content of 61.26±0.23 and 50.00±0.19 mg of GAE/gm of extractive, respectively. Different extractives of A. chaplasha and B. spectabillis showed clot lysis activity ranging from 2.56±0.68% to 17.07±0.23% and 2.24±0.71% to 17.59±0.74% as compared to 66.77% and 3.791 % produced by the standard streptokinase and water, respectively. In hypotonic solution and heat induced conditions, the crude extract of A. chaplasha inhibited the haemolysis of human erythrocyte by 41.96±0.87% and 40.00±0.78%, while the carbon tetrachloride soluble fraction of methanol extract of B. spectabillis inhibited haemolysis by 65.68±0.36% and 35.62±0.82%, respectively. Here, acetyl salicylic acid (0.1 mg/ml) was used as reference showing 72.79% and 42.12% of haemolysis of RBCs in hypotonic and heat induced conditions, respectively. Among the extractives of both plants, the crude methanol extract of A. chaplasha and the chloroform soluble fraction of B. spectabillis extract revealed mild to moderate antimicrobial activity with zone of inhibition ranging from with 7.0 to 13.0 mm. The general toxicity was determined by brine shrimp lethality bioassay where the pet-ether soluble fraction of A. chaplasha (LC50 0.781±0.36 ?g/ml) and the aqueous soluble partitionate of B. spectabillis (LC50 1.28±0.57 ?g/ml) suggested the presence of considerable bioactive principles. DOI: http://dx.doi.org/10.3329/bpj.v16i1.14493 Bangladesh Pharmaceutical Journal 16(1): 63-68, 2013